Retracted: Anti-TNFalfa for Treatment of Isolated Gastrocnemius Myositis Related to Crohn’s Disease: A Case Report - Sami, Hammi (Archives of Case Reports, 2025)
Background: Extraintestinal manifestations are prevalent among patients diagnosed with inflammatory bowel disease (IBD). Gastrocnemius Myalgia Syndrome (GMS) is a rare manifestation of IBD. The optimal treatment regimen for GMS remains to be elucidated, and current knowledge of its histological patterns is limited. Case presentation: We present a case of GMS associated with Crohn’s disease. The patient exhibited an original histological pattern characterized by nerve involvement, and the treatment plan involved the administration of adalimumab, leading to effective management of symptoms while reducing the need for steroids. Conclusion: The body of knowledge concerning gastrocnemius myalgia syndrome is limited, underscoring the need for a comprehensive international registry to facilitate more accurate diagnosis and management strategies. The use of anti-TNFalfa therapy appears to be a relevant treatment approach.